One Step Backward: A Systematic Literature Review on the Use of N-Back Tasks to Increase Working Memory for Learner in SLA - Magtana, Darline Joy (ETDC: Indonesian Journal of Research and Educational Review, 2024)
This literature review examines the role of working memory capacity (WMC) in second language acquisition (SLA) and explores potential solutions for learners with low WMC. Research shows that students with higher WMC perform better in vocabulary learning, oral fluency, and grammar. However, few studies offer strategies to help learners with lower WMC. The review highlights N-back tasks as a promising tool for improving working memory. Studies show that N-back training can enhance memory capacity but requires consistent practice for visible results. The researcher suggests incorporating N-back tasks to help students with low WMC improve their language learning skills.